2018
DOI: 10.1002/psp.2161
|View full text |Cite
|
Sign up to set email alerts
|

Sibling position, gender, and family networks in Mexican and Senegalese migration

Abstract: This paper examines the gendered roles of sibling position and network-derived social capital in Mexican and Senegalese international migration. We investigate how men's and women's migration decisions are associated with their position within the nuclear family before and after accounting for nuclear family migrant networks. Crucially, we also estimate how sibling network "effects" are gendered. We analyse 2 comparable household surveys in very distinct settings where family obligations may vary: the Mexican … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…Although both surveys oversampled individuals with a migration background, when the samples were restricted to youth with similar family migration experiences the sizes were modest. This precluded more nuanced analyses, most notably taking into account origin and destination heterogeneity in migration patterns and family networks (Lui, Riosmena, & Creighton, ). For example, it was not feasible to stratify the analysis by origin, which may have shown different outcomes for young people from regions with distinct family and cultural norms or subject to different immigration regimes in Europe.…”
Section: Methodsmentioning
confidence: 99%
“…Although both surveys oversampled individuals with a migration background, when the samples were restricted to youth with similar family migration experiences the sizes were modest. This precluded more nuanced analyses, most notably taking into account origin and destination heterogeneity in migration patterns and family networks (Lui, Riosmena, & Creighton, ). For example, it was not feasible to stratify the analysis by origin, which may have shown different outcomes for young people from regions with distinct family and cultural norms or subject to different immigration regimes in Europe.…”
Section: Methodsmentioning
confidence: 99%
“…Literature on gender and migration has shown that women and men have different social network characteristics leading to different propensities to migrate, may have different reasons for migrating, and face different conditions overseas (Constable, ; Curran & Rivero‐Fuentes, ; Eremenko & González‐Ferrer, ; Liu, Riosmena, & Creighton, ; Malmusi et al, ; Toma & Vause, ). Yet there has been no systematic comparison of transnational families and in particular of migrant mothers and fathers (Mazzucato & Dito, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Few studies have explicitly compared male and female migrants and their family behaviours (Kraus, ). Yet studies on migration and gender have shown how men and women have different motivations to migrate (Curran & Rivero‐Fuentes, ; Kanaiaupuni, ; Massey, Fischer, & Capoferro, ), migration experiences (Hondagneu‐Sotelo, ; Wong, ), opportunities in destination country contexts (Boyd & Grieco, ; Feliciano, ), social network characteristics (Curran & Rivero‐Fuentes, ; Liu et al, ; Malmusi et al, ; Toma & Vause, ), and transnational practices (Goldring, ; Itzigsohn & Giorguli‐Saucedo, ). Goldring () found that Mexican men in the United States were more involved in citizenship practices oriented towards their country of origin.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Using the MAFE household and MMP surveys, Liu, Riosmena and Creighton (2015) examine the gendered role of family position and network-derived social capital in how international migration experience is distributed within Mexican and Senegalese families and find evidence of family obligations and differential investments in children. A comparative lens and accessible and longitudinal micro-data are essential for understanding the true and complex dynamics of international migration.…”
Section: Discussionmentioning
confidence: 99%